Pengaruh Pola Asuh Orang Tua Terhadap Perkembangan Psikologi Anak di MI Riyadlatul Atfal Hulaan Menganti Gresik - Anggreine, Dewinda; Fauziyah, Evana; Leily Rahmawati Fasi (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
The family environment can be encountered by an individual for the first time since birth into the world. Wherein there is a father and a mother. The relationship with both parents has interaction or reciprocity, of course, parents want the best for the development of their children. Where parents give encouragement to children with knowledge, behavior, and values that are considered appropriate, so that children can be more independent and develop optimally. The style of knowledge applied by parents can affect the characteristics of the child, however, this is still not realized by parents. This unconsciousness can give rise to various deviations and omissions in the upbringing of the extended family environment its effect on the development of a child's psychiatricology.